2011
DOI: 10.1039/c0jm02827d
|View full text |Cite
|
Sign up to set email alerts
|

Solution-chemistry approach to graphene nanostructures

Abstract: Graphene has many novel optical and electrical properties desirable for applications in future electrooptical devices. Graphene nanostructures are especially attractive for their wide range of tunable properties. Here we describe the recent progress and challenges in the solution-chemistry approach to graphene nanostructures. This approach could not only lead to new materials with various well-defined properties, but also enable their production in large quantities.Graphene, containing a single layer of sp 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 153 publications
(130 reference statements)
0
43
0
Order By: Relevance
“…9 Such PAHs, consisting of sp 2 carbon frameworks extending over 1 nm, can be regarded as the smallest possible nanographenes, or graphene molecules. [18][19][20][21][22][23] One-dimensional extension of graphene molecules leads to ribbon-shaped nanographenes with high aspect ratios, which are called graphene nanoribbons (GNRs). [18][19][20][21][22][23] One-dimensional extension of graphene molecules leads to ribbon-shaped nanographenes with high aspect ratios, which are called graphene nanoribbons (GNRs).…”
Section: Introductionmentioning
confidence: 99%
“…9 Such PAHs, consisting of sp 2 carbon frameworks extending over 1 nm, can be regarded as the smallest possible nanographenes, or graphene molecules. [18][19][20][21][22][23] One-dimensional extension of graphene molecules leads to ribbon-shaped nanographenes with high aspect ratios, which are called graphene nanoribbons (GNRs). [18][19][20][21][22][23] One-dimensional extension of graphene molecules leads to ribbon-shaped nanographenes with high aspect ratios, which are called graphene nanoribbons (GNRs).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In another chemo-thermal approach graphene nanoribbons (GNRs) can also be formed through various heating steps from precursor monomers such as 10,100-dibromo-9,90-bianthryl monomers to first dehalogenate the monomers followed by Cyclodehydrogenation. 2,22 A drawback of this technique is that the reduced solubility of large polycyclic systems makes the formation of large graphene domains challenging. They include techniques in which small aromatic hydrocarbons are brought together to form a larger structure (graphene) through coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…12--16 Recently, a variety of strategies became also available introducing organic addends cova--lently attached onto the surface of exfoliated graphene, thus yielding soluble graphene--based materials. 17 Moreo--ver, some novel graphene--based hybrid materials, in which the unique properties of graphene are combined with those of Eu, 18 Au 19 or CdS 20 nanoparticles as well as photoactive components such as porphyrins, 21--26 pyrenes 27-- 29 and recently electroactive exTTF, 30,31 have been pre--pared and shown that photoillumination induces intrahy--brid charge--separation. However, none of those materials have been tested so far in energy conversion schemes as active components (i.e.…”
Section: Introductionmentioning
confidence: 99%